A Trace of Murder (A Keri Locke Mystery--Book #2) - Blake, Pierce (Lukeman Literary, 2017)
"A dynamic story line that grips from the first chapter and doesn't let go." --Midwest Book Review, Diane Donovan (regarding Once Gone) From #1 bestselling mystery author Blake Pierce comes a new masterpiece of psychological suspense. In A TRACE OF MURDER (Book #2 in the Keri Locke mystery series), Keri Locke, Missing Persons Detective in the Homicide division of the LAPD, remains haunted by the abduction of her own daughter. Encouraged by the new lead that has landed, the first in years, she pursues it with all that she has, determined to find her daughter and bring her back alive. Yet Keri, at the same time, receives a phone call from a frantic husband, a famed Beverly Hills plastic surgeon, who reports that his wife has been missing for two days. A wealthy socialite with no enemies and little reason to leave her life, he fears the worst has become of his wife. Keri takes on the case, assigned a new partner whom she hates, as Ray still recovers in the hospital. Her investigation leads her deep into the elite Beverly Hills world of the idle rich, to encounters with lonely housewives, and those with shopping-addicted, empty lives. Keri, in over her head in this world, becomes increasingly puzzled by the conflicting signals: did this woman, with a stalker and a lurid, secret past, run away, or was she abducted? Or did something far more sinister happen? A dark psychological thriller with heart-pounding suspense, A TRACE OF MURDER is book #2 in a riveting new series-and a beloved new character-that will leave you turning pages late into the night. "A masterpiece of thriller and mystery! The author did a magnificent job developing characters with a psychological side that is so well described that we feel inside their minds, follow their fears and cheer for their success. The plot is very intelligent and will keep you entertained throughout the book. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) Book #3 in the Keri Locke series will be available soon.
Keywords: Krimi, detektivky